The “Secret of the Creation of the Demons”: A Chapter in an Anonymous Lurianic Treatise Adapted by Moses Zacuto - Necker, Gerold (Jewish Thought, 2020)
This article questions the view that R. Moses Zacuto (ReMeZ) focused his kabbalistic efforts strictly on adapting Hayyim Vital’s version of Lurianic kabbalah. In doing so, an unknown Lurianic treatise found in an autograph of Zacuto will be specifically taken into account. The concepts of this treatise are affiliated with the school of Israel Saruq, and some of them resound in Zacuto’s work, in particular Em la Binah. The first part analyzes a chapter on the creation of demons, and addresses the issue of possible sources, which leads to the identification of an Ashkenazi tradition that was also incorporated in Vital’s Sefer ha-Liqqutim. The second part discusses one of Zacuto’s glosses on this treatise and the connection to his dictionary of magic names, Shorshei ha-Shemot.